Daya Terima Panelis Terhadap Brownies Panggang Berbahan Baku Tepung Umbi Daluga (Cyrtospermamerkussi (Hassk)(Schott) - Anastasya Melapa; Gregoria S. Djarkasi; Jenny A. Kandou; Maya M. Ludong (COCOS, 2015)
ABSTRACTBulbs Daluga (Cyrtospermamerkussi (Hassk) (Schott) is a type of local tubers in North Sulawesi region especially in Sangihe. It has high carbohydrate value that is 83.85% and 2.75% crude fiber. Processing of Daluga tubers into flour, provide opportunities of development being more varied, which indirectly helped the achievement of food security programs. As a damaged easy commodity, daluga require special prevention to extend the quality of safe,one of the main carried out is processed into flour substitution in this regard in making brownies. Brownies is a product bakery are included in the category of cake with the basic ingredients of flour. This study aimed to evaluate the acceptability of panelists to bake brownies that use raw materials substitution daluga flour. The benefit of this research is to provide information what percentage of flour that can be substituted daluga in making brownies. This study use randomized design with three replications object research, which are flour substitution treatment daluga 100% 0% wheat flour, flour daluga 80% 20% wheat flour, flour daluga 60%, 40% wheat flour, flour daluga 40% wheat flour and 20% 60% 80% daluga flour wheat flour. These results indicate that the resulting colour of the flour substitution daluga brownies are light brown, resulting from the addition of cocoa flour or cocoa powder. Taste of flour brownies daluga preferred by the panelists is caused due to components such as milk, eggs, flour and cocoa. The resulting aroma has a distinctive aroma of brownies in general. The texture of the soft and dense brownies due to additional materials such as eggs. While the expanding power is due to the heating. The greater the amount of flour, the greater the power generated expands brownies. Sensory quality or power/ test Thank Panelists most preferred is the use of 80% flour and 20% flour daluga tubers.Keywords: Wheat Daluga, Bake Brownies